Al-Nasr al-Adabi (Prosa Sastra Arab) Karakteristik, Jenis, dan Unsur-Unsur Intrinsik. - Sukron Kamil (Buletin Al-Turas, 2006)
Arabic prose is different from Indonesia spch texts, correspondences, and maqamat as a part of the  prose. Prose is generally divided into two types: imaginative and non-imaginative. All of the immaginative  literature have elements such as characters, plot, setting, theme,and beautiful language style.